Evaluation of properties and formaldehyde removal efficiency of biocarbon prepared at variable pyrolytic temperatures - Zouari, Mariem; Marrot, Laetitia; DeVallance, David Brian (Frontiers in Environmental Science, 2023)
Biocarbon (BC) represents a potential material for application in air remediation. This study investigated the efficiency of BC particles in the removal of formaldehyde. BC samples were prepared from Arundo donax (AD) and olive stone (OS) feedstocks at variable pyrolysis temperatures (from 300 °C to 800 °C). The BC particles were characterized using proximate, Fourier transform infrared, water contact angle, and physisorption analyses. The formaldehyde removal capacity was tested using an electrochemical formaldehyde sensor in a batch experiment. The physicochemical and structural properties depended on the pyrolysis temperature at which the BC was produced. The increase in pyrolysis temperature increased the BC's pH, hydrophobicity, and porosity. All the samples achieved a formaldehyde removal capacity ranging between 26% and 64% for BC pyrolyzed at 300 °C and 800 °C, respectively. In BC pyrolyzed at temperatures under 500 °C, the formaldehyde capture was governed by a partitioning mechanism through diffusion in the noncarbonized organic fraction. In comparison, formaldehyde capture was controlled by a physical adsorption mechanism through pore filling for BC pyrolyzed at 500 °C or above. BC pyrolyzed at 800 °C was more efficient for formaldehyde adsorption due to the well-developed microporous structure for both AD and OS. AD-derived BC prepared at 800 °C (AD-BC800) was selected for the re-usability test, using thermal regeneration to remove the adsorbed components. The regenerated sample maintained a comparable formaldehyde removal capacity up to four reuse cycles. Moreover, the comparison between non-activated and activated AD-BC800 revealed that physical activation significantly enhanced BC's adsorptive ability.